Potential Mediators of Oxaliplatin-Induced Peripheral Neuropathy From Adjuvant Therapy in Stage III Colon Cancer: Findings From CALGB (Alliance)/SWOG 80702. Issue 5 (10th February 2023) - Lee, Seohyuk; Ma, Chao; Shi, Qian; Kumar, Pankaj; Couture, Felix; Kuebler, Philip; Krishnamurthi, Smitha; Lewis, DeQuincy; Tan, Benjamin; Goldberg, Richard M.; Venook, Alan; Blanke, Charles; et al.
Abstract : PURPOSE: We sought to evaluate the independent and interactive associations of planned treatment duration, celecoxib use, physical activity, body mass index (BMI), diabetes mellitus, and vitamin B6 with oxaliplatin-induced peripheral neuropathy (OIPN) among patients with stage III colon cancer enrolled in a clinical trial. METHODS: We conducted a prospective, observational study of 2, 450 patients with stage III colon cancer enrolled in the CALGB/SWOG 80702 trial, randomly assigned to 6 versus 12 cycles of adjuvant fluorouracil, leucovorin, and oxaliplatin chemotherapy with or without 3 years of celecoxib. OIPN was reported using the Common Terminology Criteria for Adverse Events (CTCAE) during and following completion of chemotherapy and the FACT/GOG-NTX-13 15-17 months after random assignment. Multivariate analyses were adjusted for baseline sociodemographic and clinical factors. RESULTS: Patients assigned to 12 treatment cycles, relative to 6, were significantly more likely to experience higher-grade CTCAE- and FACT/GOG-NTX-13-reported neuropathy and longer times to resolution, while neither celecoxib nor vitamin B6 intake attenuated OIPN. Exercising ≥ 9 MET-hours per week after treatment relative to < 9 was associated with improvements in FACT/GOG-NTX-13-reported OIPN (adjusted difference in means, 1.47; 95% CI, 0.49 to 2.45; P = .003). Compared with patients with baseline BMIs < 25, those with BMIs ≥ 25 were at significantly greater risk of developing higher-grade CTCAE-reported OIPN during (adjusted odds ratio, 1.18; 95% CI, 1.00 to 1.40; P = .05) and following completion (adjusted odds ratio, 1.23; 95% CI, 1.01 to 1.50; P = .04) of oxaliplatin treatment. Patients with diabetes were significantly more likely to experience worse FACT/GOG-NTX-13-reported neuropathy relative to those without (adjusted difference in means, –2.0; 95% CI, –3.3 to –0.73; P = .002). There were no significant interactions between oxaliplatin treatment duration and any of these potentially modifiable exposures. CONCLUSION: Lower physical activity, higher BMI, diabetes, and longer planned treatment duration, but not celecoxib use or vitamin B6 intake, may be associated with significantly increased OIPN severity.